1994
DOI: 10.1002/aic.690401206
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of trichloroethylene by polyelectrolyte/surfactant complexes

Abstract: An automated vapor pressure method is used to obtain solubilization isotherms for trichloroethylene ( TCE) ( K ) with the mole fraction of TCE ( X )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Other studies regarding the solubilisation of hydrophobic compounds within PESCs were concerned with the contaminant oil trichloroethylene (TCE). They confirmed such a solubilisation behaviour of PESCs and their use allowed for enhanced separation by using colloid-enhanced ultrafiltration processes 16. Apart from that, PESCs of oppositely charged surfactant micelles and double hydrophilic polyelectrolytes have been investigated with respect to their ability to solubilize drug molecules, as for instance done for the case of the cationic copolymer poly(ethylene oxide)- g -polyethyleneimine (PEO- g -PEI) and sodium oleate 17.…”
Section: Introductionmentioning
confidence: 68%
“…Other studies regarding the solubilisation of hydrophobic compounds within PESCs were concerned with the contaminant oil trichloroethylene (TCE). They confirmed such a solubilisation behaviour of PESCs and their use allowed for enhanced separation by using colloid-enhanced ultrafiltration processes 16. Apart from that, PESCs of oppositely charged surfactant micelles and double hydrophilic polyelectrolytes have been investigated with respect to their ability to solubilize drug molecules, as for instance done for the case of the cationic copolymer poly(ethylene oxide)- g -polyethyleneimine (PEO- g -PEI) and sodium oleate 17.…”
Section: Introductionmentioning
confidence: 68%
“…The higher the K s value, the larger the affinity of the organic compound for the micelles, which improves the efficiency of the MEUF process. K s is usually considered to be independent of, or slightly dependent on, the surfactant/phenol ratio (22)(23)(24) and independent of the operation variables. It has also been reported that the value of K s is lower at high pressure (14).…”
Section: Introductionmentioning
confidence: 99%
“…Solubilization is a phenomenon in which organic compounds insoluble or sparingly soluble in water can be brought into aqueous solutions by addition of appropriate surfactants. A large number of investigations of the solubilization of organic compounds into micelles have been reported in the open literature. The partition coefficient of an organic compound between continuous and dispersed phases is a thermodynamically important parameter and has been measured by many different methods, such as vapor pressure, , semiequilibrium dialysis, head-space chromatography, NMR spectroscopy, UV−vis spectral methods, , and fluorescence probes . Esumi et al .…”
Section: Introductionmentioning
confidence: 99%
“…A large number of investigations of the solubilization of organic compounds into micelles have been reported in the open literature. [12][13][14][15][16][17][18] The partition coefficient of an organic compound between continuous and dispersed phases is a thermodynamically important parameter and has been measured by many different methods, such as vapor pressure, 19,20 semiequilibrium dialysis, [21][22][23][24][25][26][27][28] head-space chromatography, 29 NMR spectroscopy, 30 UV-vis spectral methods, 31,32 and fluorescence probes. 33 Esumi et al 34 studied the adsolubilization of hexanol into dodecylpyridinium chloride (DPCl) or cetylpyridinium chloride (CPCl) bilayers on negatively charged silica.…”
Section: Introductionmentioning
confidence: 99%